Burden of non-communicable diseases in South Asia: a decomposition analysis - Jalandhar Pradhan; Manacy Pai; Rinshu Dwivedi; Bijeta Mishra; Sasmita Behera; Tapas Bera; Rockli Kim; S. V. Subramanian (Journal of Health, Population and Nutrition)
Abstract Background This study examines the incidence, prevalence, deaths, and disability-adjusted life years (DALYs) related to non-communicable diseases (NCDs) in South Asia, exploring the environmental, metabolic, and behavioural risk factors, and exploring changes in deaths and DALYs driven by population growth, aging, and mortality rates. Methods Using data from the Global Burden of Disease (GBD) study 2021, we estimated age-standardized incidence, prevalence, deaths, and DALYs for four major NCDs: cardiovascular diseases, cancer, diabetes, and chronic respiratory diseases from 2010 to 2021. Gender and age-specific estimations were conducted across all NCDs, with 95% uncertainty intervals and a decomposition analysis was employed to estimate change in death and DALYs attributable to NCDs. Findings The burden of NCDs in South Asia increased by 3.00% in incidence from 2010 to 2021, while overall prevalence decreased by 1.00%, yet the age-standardized prevalence rate remains above the global rate (91,570 per 100,000 population). Incidences of cardiovascular and respiratory diseases declined by 3.00% and 13.00%, respectively, whereas diabetes and cancer rose by 21.00% and 13.00% in South Asia. Nepal faced the highest environmental impact (23.4% of DALYs), Bangladesh the greatest metabolic impact (25.62%), and India the highest from behavioural factors (23.95%). Population growth and aging were primary drivers of changes in deaths and DALYs across the region. Conclusion This finding emphasizes the need for targeted public health interventions addressing environmental, metabolic, and behavioral risks for NCDs in South Asia, alongside strategies to support healthy aging and effective disease management across diverse demographic groups.